Feature Selection In The Human Aspect of Information Security Questionnaires Using Multicluster Feature Selection - Valentina Siwi Saridewi, Riri Fitri Sari (International Journal of Advanced Science and Technology, 2020)
The human aspect is a major vulnerability in information security that relates toknowledge, attitude, and behavior in information security. This study aims to determinethe essential variables used to assess the level of information security in a person. Thisstudy used Principal Component Analysis (PCA) and Multicluster Feature Selection(MCFS) approaches. Data collection using questionnaires based on The Human Aspectsof Information Security Questionnaire (HAIS-Q) with adaptation to the Indonesianenvironment. The questionnaire distributed to 148 employees at XYZ institution asrespondents. The level of information security applied to each individual based on theresult of respondents' responses to the questionnaire. Data processing has beenconducted using the Python programming language and Notebook Juypter as tools. Theaim of PCA is to help in reducing some features with a specific explained variance ratio.MCFS is used to help reduce the number of features which can represent all features onHAIS-Q. The selected features based on knowledge are password security, social media,mobile device, and incident report. The selected features based on personal attitudes arepassword security, email usage, internet usage, mobile device, information handling, andincident reporting. The selected features based on behavior are password security, emailused, internet used, mobile device, information handling, and incident reporting